Student Response to Booklet Learning Media Butterfly Pea Flower (Clitoria ternatea L.) - Tenriawaru*, Andi Besse; Panjaitan, Ruqiah Ganda Putri; Caiping, Zhu (Jurnal Pendidikan Sains Indonesia, 2024)
Learning media is a means to facilitate teachers in providing material, create enthusiastic and motivated students in accomplishment learning, therefore can be improve their abilities and skills in receiving the learning provided. The utilization of booklets as learning media creates interest in learning and a positive response. This study aims to find out the students' response to the booklet of butterfly pea plant (Clitoria ternatea L.) as a learning media. The instrument used was a questionnaire with three aspects of response, namely affective, cognitive, and conative which existed additional developed into 11 statements items. The average percentage obtained for each aspect of response, namely affective, cognitive, and conative response aspects, was 75,89%; 67,11%; 70,98% with the overall response having an average of 71,33%. It can be concluded that the booklet developed into learning media received a positive response from students